2015
DOI: 10.1103/physreve.91.052904
|View full text |Cite
|
Sign up to set email alerts
|

Farey sequence in the appearance of subharmonic Shapiro steps

Abstract: The largest Lyapunov exponent has been examined in the dynamical-mode locking phenomena of the ac+dc driven dissipative Frenkel-Kontorova model with deformable substrate potential. Due to deformation, large fractional and higher order subharmonic steps appear in the response function of the system. Computation of the largest Lyapunov exponent as a way to verify their presence led to the observation of the Farey sequence. In the standard regime, the appearance of half-integer and other subharmonic steps between… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 32 publications
0
22
1
Order By: Relevance
“…Detailed explanation of our approach and numerical procedure can be found in Ref. [27]. In further text, we will refer to the quantity of largest Lyapunov exponent as the Lyapunov exponent (LE) for convenience.…”
Section: Modelmentioning
confidence: 99%
“…Detailed explanation of our approach and numerical procedure can be found in Ref. [27]. In further text, we will refer to the quantity of largest Lyapunov exponent as the Lyapunov exponent (LE) for convenience.…”
Section: Modelmentioning
confidence: 99%
“…The new term with the force F is often named dc driving (dc: direct current) [2,58]. In many applications it is further subdivided in the dc-part, F dc , and an ac-part (alternating current) [30,32]. It is F ac cos(c t) with a constant c and a time variable t. The force tilts the former on-site potential with the incline F .…”
Section: Tilting Of the Fk Modelmentioning
confidence: 99%
“…The two edge-driven forces are given, but the internal movement of the chain is a black box. This direction is sometimes 'quite better' for NTs than others, like the only push direction, (1,0,...,0) T , or the only-pull direction, (0,...,0,1) T , or an equal force [30,32] to all particles, the direction (1,1,...,1,1) T , making a tilted washboard potential. 'Quite better' here means the property of the corresponding NT to find a minimum energy pathway (MEP) through the PES mountains, or at least a similar low energy path (LEP).…”
Section: Introductionmentioning
confidence: 99%
“…Remoissenet and Peyrard [47,48] proposed deformable models of nonlinear systems with deformable periodic substrate potential V RP (x, r), where the parameter, r is the deformable po-tential parameter which determines the shape of the potential. The potential V RP (x, r), now often known as the Remoissenet-Peyrard-potential, plays a significant role in one-dimensional atomic chains and has become a subject of diverse research focus [49][50][51][52][53][54][55][56][57][58][59][60][61]. Earlier studies, for instance, Nana, et al [49] used Melnikov theory to predict the onset of chaotic behaviour of a particle in an asymmetric doubly-periodic potential.…”
Section: Introductionmentioning
confidence: 99%
“…Mali et al [53] observed the appearance of large subharmonic Shapiro steps due to deviations from the sinusoidal potential. More recently, stochastic resonance [54], Farey sequences and Shapiro steps [55], anomalous transport and diffusion phenomena [56][57][58], current reversals [59], and jump diffusion [60], as well as Devil's staircases [61], have all been investigated. In general, the dynamical and statistical properties are strongly dependent on the variation of the biharmonic parameter, the shape parameter and the phase-lag.…”
Section: Introductionmentioning
confidence: 99%